2015
DOI: 10.5433/1679-0359.2015v36n3p1609
|View full text |Cite
|
Sign up to set email alerts
|

Balanço de nitrogênio em cordeiros alimentados com rações contendo diferentes teores de concentrado

Abstract: ResumoAvaliou-se o consumo, a produção fecal e urinária de nitrogênio e o balanço de nitrogênio (BN) em cordeiros alimentados com diferentes teores de concentrado (20,0%, 40,0%, 60,0% e 80,0%) na região sudoeste do estado de Mato Grosso. Foram utilizados quatro cordeiros sem raça definida (SRD), inteiros, com peso corporal (PC) médio de 19,3 kg ± 2,1 alocados em gaiolas de metabolismo, alimentados duas vezes ao dia. O concentrado foi composto por grão de milho moído e farelo de soja e o volumoso fornecido foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
10
0
3
Order By: Relevance
“…Moreno et al (2010) observed a N intake of 32.60 g day -1 for sheep fed with 60% concentrate containing 19.0% CP. Geron et al (2015) found values of 12.38 g day -1 working with 40% concentrate containing 13.0% PB.…”
Section: Resultsmentioning
confidence: 92%
“…Moreno et al (2010) observed a N intake of 32.60 g day -1 for sheep fed with 60% concentrate containing 19.0% CP. Geron et al (2015) found values of 12.38 g day -1 working with 40% concentrate containing 13.0% PB.…”
Section: Resultsmentioning
confidence: 92%
“…Fecal collecting bags were attached to each animal 5 d before fecal collection in each experimental period. Management of the animals during the adaptation and collection periods followed the protocol described by Geron et al (2015a).…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of N in the sheep urine were determined using the Kjeldahl method, as described by Silva and Queiroz (2002), and NB was estimated using the formula NB = [N provided g -N of the leftovers g) -(N in feces g + N in urine g)], as described by Geron et al (2015a). The amount of N absorbed (NA) by sheep was calculated using the equation NA = [(N provided g -N of the leftovers g) -(N in the feces g)] and N intake (NI) was estimated using the equation NI = [(N provided g -N in leftovers g)], as described by Moreno et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Several factors can affect the extent of CP degradation in the rumen, including the chemical and physical composition of the CP, microbial proteolytic activity, access of bacteria to protein, food retention time in the rumen, ruminal pH, food processing, ambient temperature, and modifying substances of ruminal fermentation ( VAN SOEST, 1994;GERON et al, 2015).…”
Section: Introductionmentioning
confidence: 99%